Mutual Fund Flows, Performance Persistence, and Board Quality - LAI, Sandy (Institutional Knowledge at Singapore Management University, 2010)
This paper provides evidence on the impact of fund board quality on (a) the fund flow-performance relation, (b) persistence in fund performance, and (c) a fund’s potential change of strategy following a period of underperformance. We use Morningstar’s board quality ratings as a proxy for the quality of the fund’s board and document three main results. One, we show that funds that rank in the bottom quintile of rankings based on past performance, experience significantly lower flows at the margin when their board quality rating is poor compared to when the board quality is rated as good. Two, we document a significant relationship between board quality and short-term performance persistence. For funds with bad boards, a negative past alpha predicts future negative alpha but the evidence of positive performance persistence is much weaker than for funds with good boards. Three, we show that a change in fund strategy following poor performance is more likely for funds with good boards compared to funds with bad boards. These findings extend the Lynch and Musto (2003) hypothesis that suggests that funds may discard those strategies which underperformed in the past. Our contribution is to show that it is the good quality boards that are more likely to affect a change of strategy. Hence, the quality of a fund’s board has an important influence on the incentive to change a fund’s strategy. Taken together our results suggest that recent attempts to provide qualitative information to fund shareholders on dimensions of fund governance quality are indeed warranted and quite valuable from the standpoint of investor decision making.